Risk of venous thromboembolism in hospitalised cancer patients in England – A cohort study - Ratib, Sonia; Walker, Alex J.; Card, Timothy R.; Grainge, Matthew J. (BioMed Central, 2016)
Background: Venous thromboembolism (VTE) is a well-recognised and life-threatening complication in patients with cancer. However, the precise risk of VTE in hospitalised cancer patients in England has not been previously reported.